The Effect of Leadership and Work Discipline on Employee Performance: A Study in Sinsing Dekorasi Yogyakarta - Burhanudin; Rahamusa, Wafi Putra; Mahmudah, Nur (International Journal of Business and Applied Economics, 2024)
This study aims to: (1) examine the influence of leadership on employee performance; and (2) examine the effect of work discipline on employee performance. The population in this study were 37 employees of Singsing Decoration Yogyakarta. The data collection technique used a questionnaire, while the data analysis technique used multiple regression analysis. The results of the study found that leadership has a positive influence on employee performance, and work discipline has a positive influence on employee performance.